Anomalous Raman Scattering In Few Monolayer MoTe2. (16th January 2017) - Gołasa, Katarzyna; Grzeszczyk, Magdalena; Molas, Maciej R.; Zinkiewicz, Małgorzata; Nogajewski, Karol; Potemski, Marek; Wysmołek, Andrzej; Babiński, Adam
ABSTRACT: The effect of temperature (5K to 300K) on the Raman scattering due to A1g /A1 ' modes associated with the out-of-plane vibrations in bilayer (2L) and trilayer (3L) MoTe2 is investigated. The temperature evolution of the modes critically depends on the flake thickness. The A1g mode intensity in 2L MoTe2 observed with λ=632.8 nm light excitation decreases with decreasing temperature down to 220K and the mode vanishes from the Stokes scattering spectrum in the temperature range between 160K and 220K. The peak recovers at lower temperatures and at T =5K it becomes three times more intense that at room temperature. Similar non-monotonic intensity evolution is observed for the A1 ' mode in 3L MoTe2 in which tellurium atoms in all three layers vibrate in-phase. On the contrary, the intensity of the other out-of-plane Raman-active mode in which vibrations of tellurium atoms in the central layer of 3L MoTe2 are shifted by 180° with respect to vibrations in outer layers, only weakly depends on temperature. The observed quenching of the out-of-plane modes in the Raman scattering in thin MoTe2 layers is related to the destructive interference of the resonant- and the non-resonant contributions to the Raman scattering. The resonance with the M point of the Brillouin zone in few-layers of MoTe2 is considered. Effects related to the resonant quenching of the in-phase out-of-plane mode are discussed.